2019
DOI: 10.1063/1.5083711
|View full text |Cite
|
Sign up to set email alerts
|

Propagation properties of sub-millimeter waves in foggy conditions

Abstract: The propagation of millimeter (MMW) and submillimeter (terahertz, THz) waves in the atmosphere is subject to absorptive and dispersive effects. The resulting attenuation and temporal group delay increase in cloudy and hazy weather. In this work, the effects of water droplets suspended in the air on the propagation of electromagnetic radiation in submillimeter waves are studied theoretically and experimentally. A comparison is made between the link budget in THz frequencies and the expected attenuation for free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…The model was tested experimentally for various foggy conditions in a controlled environment demonstrating good agreement with measured results [9][10][11].…”
Section: Propagation Factors Of the Atmospherementioning
confidence: 58%
See 1 more Smart Citation
“…The model was tested experimentally for various foggy conditions in a controlled environment demonstrating good agreement with measured results [9][10][11].…”
Section: Propagation Factors Of the Atmospherementioning
confidence: 58%
“…The signal phase shift and time delay effects are usually ignored, although they can be significant in extreme conditions [5,6]. Pinhasi et al presented in their previous studies on MMW atmospheric propagation, theoretical and experimental results of absorptive and dispersive propagation effects and their influence on the signal strength and phase dispersion [7][8][9][10][11]. It was found that apart from attenuation, the dispersive effects like group delay should be considered in the design of MMW and THz radar and wireless communication links.…”
Section: Introductionmentioning
confidence: 99%
“…where ε W and ε W are the real and imaginary parts of the dielectric permittivity of the suspended water (in distinction to the permittivity of the medium, ε (f ) as in (3)), and η (f ) = [2 + ε W (f )] /ε W (f ). The quantities in detail can be found in [2,3,6].…”
Section: Propagation In Dielectric Mediamentioning
confidence: 99%
“…Models are used to study the effect of clouds and fog on the electromagnetic signal, in particular the attenuation and time delay [4][5][6]. Recently, experimental study in ultra-low visibility artificial fog in a confined space was performed using an artificial fog produced by a "smoke machine" [7].…”
Section: Introductionmentioning
confidence: 99%
“…It was not feasible to conduct well-controlled tests in an open atmosphere, and because experimental work requires a stable and homogenous environment, we therefore measured and characterized LIDAR performances inside an aerosol chamber. Such facilities provide well-defined degraded atmospheric environments, with a wide range of droplet size distributions and visibility ranges [ 6 , 16 , 17 ]; for example, a previous study has successfully been conducted in our fog chamber [ 18 ]. This section also presents the experimental results adjoined with a comparison to the expected radiative transfer calculations results according to our proposed model.…”
Section: Introductionmentioning
confidence: 99%